THE ROLE OF STORYTELLING IN LANGUAGE DEVELOPMENT IN CHILDREN AGED 4–6 YEARS - Riyan Maulana; Saddam (CV Naskah Aceh, 2025)
Speaking ability is one aspect of language development that can be optimized at an early age. Storytelling is one method to optimize speaking ability in early childhood. This study aims to describe the role of storytelling activities on early childhood speaking ability. The approach used in this study is descriptive qualitative, with document analysis and observation methods. Primary data sources come from books and scientific journals related to storytelling and early childhood speaking skills, while secondary data sources come from 4-year-old children. The results of the study indicate that storytelling has three components: the storyteller, the storyteller, and the listener. Stories are a medium to teach vocabulary and sentences for children to listen to, so that children will be encouraged to say the words or sentences they hear. Storytelling can foster new attitudes so that responses emerge in the form of words or sentences, make children recognize environmental conditions so they can respond using words or sentences, and foster a desire to express opinions.